Proceedings of the Annual Symposium on Computer-Human Interaction in Play 2017
DOI: 10.1145/3116595.3116631
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Player Experience without the Player.

Abstract: A key challenge of procedural content generation (PCG) is to evoke a certain player experience (PX), when we have no direct control over the content which gives rise to that experience. We argue that neither the rigorous methods to assess PX in HCI, nor specialised methods in PCG are sufficient, because they rely on a human in the loop. We propose to address this shortcoming by means of computational models of intrinsic motivation and AI game-playing agents. We hypothesise that our approach could be used to au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…[63], for instance, takes a Monte-Carlo approach to evaluating diversity and playability by observing the scores of a large number of simple AI players. In contrast, [126] and [46] apply models of game experience that originate from related research, namely the concepts of flow and empowerment. In [46], the employed model is also verified using explicit quantitative and qualitative feedback from human players.…”
Section: A22 Platformersmentioning
confidence: 99%
“…[63], for instance, takes a Monte-Carlo approach to evaluating diversity and playability by observing the scores of a large number of simple AI players. In contrast, [126] and [46] apply models of game experience that originate from related research, namely the concepts of flow and empowerment. In [46], the employed model is also verified using explicit quantitative and qualitative feedback from human players.…”
Section: A22 Platformersmentioning
confidence: 99%
“…Our focus here is on algorithmic player modeling, i.e., approaches that explicitly implement behavioral laws and do not need extensive datasets, except possibly for parameter tuning. Such approaches offer greater flexibility of deployment, especially regarding automated testing and balancing of new games or game features for which data from human players is not yet available [24]. For a broader review of player modeling and the use of AI techniques in player modeling, we refer the reader to the work of Yannakakis and Togelius [93,94,95].…”
Section: A Note On Scopementioning
confidence: 99%
“…In summary, the excluded papers 1) did not propose or test any computational motivation model that can be implemented in a game-playing agent, or 2) used data-driven models that cannot necessarily be reapplied when game parameters change without collecting new data from human players [24]. On the other hand, we included papers that focus on non-player characters (NPCs) instead of simulated players; if such NPCs can generate plausible human-like behavior, the underlying techniques should be relevant for player modeling as well.…”
Section: A Note On Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is also the question to which extent a player's empowerment in a game can be used as predictor for their experience. A preliminary study [5] identified causal efficacy as potential candidate experience that empowerment is closely related to, with mediate effects on "challenge, involvement, attention and engagement, learning and emotions". Having a measure that computes user experience without an actual player would be beneficial in rapid prototyping and when creating or adapting games automatically.…”
Section: A Motivationmentioning
confidence: 99%